Pengaruh Selebgram dan Lifestyle Terhadap Minat Beli Mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang: (Studi Pada Mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang) - Jaya Sanderu (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2022)
This study aims to analyze the effect of celebgram and lifestyle on student buying interest. Respondents in this study were management students at the University of PGRI Semarang with a total of 100 respondents. The data process is carried out by collecting data online by distributing questionnaires via Google Drive. This study uses quantitative methods with data techniques through questionnaires and observations. The method used in this study is multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between celebgrams on purchase intention and a positive and significant influence between lifestyle on purchase intention. Celebgram and lifestyle simultaneously influence buying interest. Based on the results of the research conducted, it was found that the R Square value was 0.386 or 38.6%. While the remaining 0.614 or 61.4% was found by other variables not examined in this study.